2021
DOI: 10.1186/s13063-021-05101-2
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of the erector spinae plane (ESP) block for quality of recovery in posterior thoraco-lumbar spinal decompression surgery: study protocol for a randomised controlled trial

Abstract: Background Spinal surgery can be associated with significant postoperative pain. Erector spinae plane (ESP) block is a new regional anaesthesia technique, which promises effective postoperative analgesia compared with systemically administered opioids, but has never been evaluated in terms of patient-centred outcomes such as quality of recovery and overall morbidity after major thoraco-lumbar spinal surgery. Methods We are conducting a prospective,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…Of the 15 trials included [ 6 – 8 , 12 23 ], one [ 17 ] involved free-hand ESPB, while the others [ 6 – 8 , 12 16 , 18 23 ] were ultrasound-guided (USG-guided) ESPB. The main local anesthetics used included bupivacaine [ 6 – 8 , 12 14 , 16 , 18 , 19 ], ropivacaine [ 20 23 ], levobupivacaine [ 15 ], and mixtures of bupivacaine and lidocaine [ 17 ]. The features of the included trials are shown in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Of the 15 trials included [ 6 – 8 , 12 23 ], one [ 17 ] involved free-hand ESPB, while the others [ 6 – 8 , 12 16 , 18 23 ] were ultrasound-guided (USG-guided) ESPB. The main local anesthetics used included bupivacaine [ 6 – 8 , 12 14 , 16 , 18 , 19 ], ropivacaine [ 20 23 ], levobupivacaine [ 15 ], and mixtures of bupivacaine and lidocaine [ 17 ]. The features of the included trials are shown in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…All trials described the random sequence generation methodology, and six trials [ 7 , 8 , 10 , 13 , 20 22 ] described allocation concealment methods used. Four trials [ 15 , 17 19 ] described the blinding of participants and personnel, while one trial [ 13 ] did not mention blinding of outcome assessment. Complete data were available in all included studies, with no selective reporting or bias.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations